PEMANFAATAN LIMBAH BONGGOL JAGUNG UNTUK BAHAN DASAR PEMBUATAN BRIKET/ARANG SEBAGAI POTENSI ENERGI ALTERNATIF - Lita Nasution (Universitas Negeri Medan, 2023)
The limited utilization of corn cob waste by the community can be linked to a lack of awareness and understanding, leading to a minimal level of concern for its proper management. The conversion of corn cobs, which are a plentiful waste material, into briquettes has proven to be a viable method of harnessing alternative energy. Hence, there is a need to undertake a socialization effort aimed at educating the general public regarding the utilization of maize cobs as a viable raw material for the production of briquettes and charcoal, thereby presenting a promising alternative energy source. briquettes, also known as biocharcoal, is regarded as a sustainable biomass energy resource with minimal environmental impact. In addition, briquettes are also easily produced and possess a high calorific value. briquettes showing potential significant alternative energi with high innovation. The community engagement activity serves as a valuable means of educating and motivating the community of Dusun VIII in Kolam Village to foster collaboration with the objective of diminishing trash production and harnessing its potential, while also disseminating knowledge regarding self-generated alternative energy sources. The approach utilized in the execution of this program is direct observation.Â Keywords: alternative energi; charcoal briquettes; corncob